A General and Highly Selective Palladium‐Catalyzed Hydroamidation of 1, 3‐Diynes. Issue 1 (27th October 2020) - Liu, Jiawang; Schneider, Carolin; Yang, Ji; Wei, Zhihong; Jiao, Haijun; Franke, Robert; Jackstell, Ralf; Beller, Matthias
Abstract: A chemo‐, regio‐, and stereoselective mono‐hydroamidation of (un)symmetrical 1, 3‐diynes is described. Key for the success of this novel transformation is the utilization of an advanced palladium catalyst system with the specific ligand Neolephos. The synthetic value of this general approach to synthetically useful α‐alkynyl‐α, β‐unsaturated amides is showcased by diversification of several structurally complex molecules and marketed drugs. Control experiments and density‐functional theory (M06L‐SMD) computations also suggest the crucial role of the substrate in controlling the regioselectivity of unsymmetrical 1, 3‐diynes. Abstract : The advanced Pd catalyst system with Neolephos as a ligand enables highly selective hydroamidation of unbiased (un)symmetrical 1, 3‐diynes. In this way, a wide range of synthetically useful α‐alkynyl‐α, β‐unsaturated amides are afforded in good to high yields with excellent chemo‐, regio‐, and stereoselectivities.